A study of the practical challenges associated with developing a new test for bovine tuberculosis - Pirovano, Andrea (2019)
Bovine tuberculosis, a chronic disease caused by Mycobacterium bovis, is a major economic problem affecting farmers both in the UK and worldwide. In order to prevent and control bovine tuberculosis it is very important to be able to promptly and definitively diagnose infected animals. However, the current diagnostic tools show some limitations which can contribute to cause economic losses and to the transmission of the disease to other animals in a herd, to wildlife and potentially to humans. Therefore, there is an urgent need to have available new diagnostic methods that allow the definitive detection of bovine tuberculosis. In this work, the practical issues associated with the cost-effective production of two diagnostic kits that employ mycobacteriophage (ActiphageTM and ActiphageTM Rapid) were investigated. This technology exploits the ability of bacteriophage to infect live mycobacterial species in a strain specific manner. This technique was originally developed as a tool for the diagnosis of human tuberculosis (FastPlaqueTBTM, BIOTEC) and has now been refined to offer transformational tools with significant applications in veterinary, agriculture and - potentially – the human sector. These kits are manufactured and distributed by PBD Biotech Ltd. (Thurston, Suffolk, UK) and allow the detection of the presence of M. bovis and M. avium subsp. paratuberculosis in diverse sample types, such as blood and milk. The assays can therefore be used for infection control and as a part of a quality assurance programme to confirm the absence of these organisms in non-pasteurized dairy products. Furthermore, the methods can be adapted to detect other types of mycobacteria and applied to detect infection not only in cattle but also in other animal hosts including sheep, goats, deer, horses, alpacas, llamas as well as companion animals and exotic species.